The structural, electronic and optical properties of four α-Se-based heterostructures with hyperbolic characteristics. Issue 36 (7th September 2022) - Zhao, Chunxiang; Wang, Jiaqi; Cai, Xiaolin; Wang, Panpan; Zhu, Zhili; Niu, Chunyao; Jia, Yu
Abstract : Four novel α-Se-based van der Waals heterostructures have been systematically studied, and the unveiled electronic and optical properties suggest that they are promising to be used in electronic and optoelectronic devices. Abstract : The physical properties and potential applications of two-dimensional (2D) materials can be effectively modulated and enriched by constructing van der Waals heterostructures (VDWHs) with two or more 2D monolayer materials. In this work, by using first-principles calculations based on density functional theory (DFT), we have systematically investigated the structural, electronic and optical properties of four α-Se-based VDWHs, that is, α-Se/Ca(OH)2, α-Se/GaSe, α-Se/h-BN and α-Se/MoS2 VDWHs. The results show that both the band alignment and band gap of these four VDWHs can be effectively modulated by interlayer coupling, biaxial strain and an external electric field. Compared with interlayer coupling and biaxial strain, the external electric field can modulate the electronic properties of these VDWHs more significantly, which makes them exhibit more rich electronic properties. Interestingly, the optical property calculations revealed that both α-Se and the four α-Se-based VDWHs have intrinsic hyperbolic properties. In addition, compared with the individual components, the optical absorption of these four VDWHs in the visible and ultraviolet light regions is significantly enhanced. These results enrich the properties of selenene and selenene-based VDWHs and extend their potential applications in electronic and optoelectronic devices.